2020
DOI: 10.1097/pcc.0000000000002441
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for Teaching Cardiac Point-of-Care Ultrasound: An Exploratory Application of the Design-Based Research Approach*

Abstract: Objectives: To develop a competency-based educational tool for cardiac point-of-care ultrasound image interpretation using the design-based research approach. Design: In accordance with design-based research, multiple methods were used to determine that learners would benefit from achieving competency in cardiac point-of-care ultrasound image interpretation before they attempted it at the bedside. A competency-based educational tool was designed and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…This is in contrast to the other applications, where even though there may be different methods to acquire a view, ultimately, the video and still images present the anatomy in a similar way. We also found that poor cardiac function and cases with abnormal ventricles were among the most difficult to diagnose, which is consistent with prior research in this area 11 . This may be related to the low a priori skill in this type of pathology from bedside encounters and relatively few of these case examples in education interventions.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is in contrast to the other applications, where even though there may be different methods to acquire a view, ultimately, the video and still images present the anatomy in a similar way. We also found that poor cardiac function and cases with abnormal ventricles were among the most difficult to diagnose, which is consistent with prior research in this area 11 . This may be related to the low a priori skill in this type of pathology from bedside encounters and relatively few of these case examples in education interventions.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that poor cardiac function and cases with abnormal ventricles were among the most difficult to diagnose, which is consistent with prior research in this area. 11 This may be related to the low a priori skill in this type of pathology from bedside encounters and relatively few of these case examples in education interventions. Other diagnostically challenging cases were subtle imaging findings such as foreign bodies with respective acoustic shadowing/reverberation or the presence of lung sliding/lung point suggesting a pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations